Analysis of Minimum Service Standards (SPM) in the Education Sector in Brebes Regency - Nadia Primaswari; Ipik Permana; Hery Nariyah (Riviera Publishing, 2026)
The fulfillment of Minimum Service Standards (SPM) in education represents a fundamental responsibility of local governments in guaranteeing citizens' basic educational rights. Despite this mandate, the achievement of the Education MSS in Brebes Regency during the 2022–2024 period has remained relatively low and shown limited progress compared to other basic service sectors. This study aims to examine the implementation of Minimum Service Standards in the education sector in Brebes Regency and analyze the factors influencing its performance. The research applies a qualitative descriptive approach using a case study design. Data were collected through interviews, observations, and document analysis involving relevant local government institutions. The analysis is guided by public policy implementation theory and the Total Quality Management (TQM) framework to assess service quality, coordination, and organizational commitment. The findings indicate that the implementation of Education MSS has not yet achieved optimal outcomes, particularly in early childhood education and equivalency education services. The main constraints include weak data processing, ineffective inter-agency coordination, limited resources in terms of both teaching staff and technical personnel, and suboptimal integration of regional development planning. Meanwhile, supporting factors consist of regulatory clarity, local government commitment, and utilization of the e-MSS system. This study concludes that strengthening policy implementation mechanisms and applying continuous improvement principles are key to enhancing the performance of Minimum Service Standards in the education sector at the local level